A Case of Acquired Reactive Perforating Dermatosis with Complete Resolution of Eruptions on Upper and Lower Limbs During the Treatment of Diabetes Mellitus and Peripheral Artery Disease - Yoshihito Mima; Tsutomu Ohtsuka; Ippei Ebato; Ryosuke Nishie; Satoshi Uesugi; Makoto Sumi; Yoshimasa Nakazato; Yuta Norimatsu (Medicina)
Acquired reactive perforating dermatosis (ARPD) is characterized by its onset after the age of 18 years, umbilicated papules or nodules with a central keratotic plug, and the presence of necrotic collagen tissue within an epithelial crater. ARPD is strongly associated with systemic diseases such as diabetes mellitus (DM) and chronic renal failure, which may contribute to ARPD through factors including microcirculatory disturbances and the deposition of metabolic byproducts, including advanced glycation end-products and calcium. Here, we report a case of ARPD that improved following DM treatment and catheter-based interventions for peripheral artery disease (PAD). The eruptions on the upper limbs significantly improved with DM management. On the other hand, lesions on the lower limbs showed marked improvement after the enhancement in arterial blood flow due to catheter surgeries, along with DM treatment. Although a few reports of ARPD improving with DM management exist, our case underscores the importance of adequate DM control in ARPD management. The inability to perform the biopsy of the lesions on the lower limbs is our limitation; however, these lesions, similar to those on the upper limbs, presented with a central keratotic plug and re-epithelialized without forming ulcers or erosions, suggesting they were also related to ARPD. To date, there has been little discussion on the relationship between blood flow impairment in major vessels and ARPD. However, hypertension and venous circulatory dysfunctions are considered to lead to ARPD, raising the possibility that PAD-induced microvascular disturbances might have facilitated lesion formation in the present case. Further accumulation of cases and research is needed to clarify the relationship between blood flow impairment in major vessels and ARPD.